Orthodontic treatment need switch quality of life based on oral health impact profile-14 in adolescents (study in Barru District): Hubungan kebutuhan perawatan ortodontik dengan kualitas hidup berdasarkan oral health impact profile-14 pada remaja (studi di Kabupaten Barru) - Muslihin; Ardiansyah S. Pawinru; Baharuddin M. Ranggang (Makassar Dental Journal PDGI Makassar, 2020)
Background: Malocclusion is one of the important issues in the field of dental health, especially in Indonesia. The results of Riskesdas 2013 in South Sulawesi showed number of dental-mouth problems in the age group of 10-14 years was 36.9% and 15-24 years was 37.4%, with the population having abnormal dental function as much as 3.26%, and 60% received orthodontic treatment, especially in Barru District about 40%. This situation is the base of researchers to conduct research on the relationship between orthodontic treatment needs and the quality of life of high school students in Barru District. Objective: To find out the relationship between orthodontic treatment needs and quality of life in adolescent high school students in Barru District. Method : An observation alanalytic study with across-sectional design using subjects was high school students in Barru District aged 15-17 years with the sampling technique was purposive random sampling of 200 students. An examination of the need for orthodontic treatment was carried out using an IOTN index and an assessment of quality of life using the OHIP-14 index. Results: This study shows that the level of orthodontic treatment need has a significant relationship based on the Spearman IOTN-DHC correlation analysis (p<0.05), while the IOTN-AC shows no significant relationship between care needs and quality of life (p>0.005). Conclusion: The need for orthodontic treatment has a significant relationship with adolescent quality of life in a positive correlation (r=0.490) which means that the higher the value of IOTN-DHC, the higher the person's discomfort.